Klinische Sportmedizin - Laszlo R; Radermacher M; Lesevic H; Steinacker JM (Dynamic Media Sales Verlag, 2017)
The case of a second look concerning indication for pacemaker implantation due to advanced AV block in a 53-year-old master triathlete is reported. An extrinsic etiology (vagal induction) of the block seemed to be possible in the initial Holter-ECG. Therefore, further diagnostics followed. In repeated Holter-ECG, there was evidence for an at least partly intrinsic etiology of the blocks. This was supported by the MRT image of a previous myocarditis and the athlete`s age so that pacemaker implantation was also finally recommended.According to the Seattle criteria, advanced AV-blocks are unusual, not-training-induced ECG alterations, even in endurance-trained athletes. Pathogenically, an intrinsic etiology (direct AV nodal impairment) has to be distinguished from an extrinsic one (affection of electrophysiological characteristics by exogenous factors such as vagotonic increase in athletes). Several ECG-criteria are availablefor differentiation. However, the whole clinical picture has to be taken into account. Clarifying the cause of AV conduction disturbances is important as according to current guidelines of the European Society of Cardiology, etiology plays a role in decision-making concerning pacemaker indication. Possibly, there is no indication if the cause is purely extrinsic.Careful clinical evaluation of athletes presenting with advanced AV blocks, takingspecial sports-cardiological and rhythmological aspects into consideration for reliable confirmation of an intrinsic and not only extrinsic/vagally induced AV conduction disturbance is important in order to possibly prevent unnecessary pacemaker implantation.KEY WORDS: AV-Block, Athlete, Pacemaker, Vagotone